Regulation of Pannexin 1 Surface Expression by Extracellular ATP: Potential Implications for Nervous System Function in Health and Disease - Swayne, Leigh A.; Boyce, Andrew K. J. (Frontiers in Cellular Neuroscience, 2017)
Pannexin 1 (Panx1) channels are widely recognized as ATP release channels, and as follows, their function is closely tied to that of ATP-activated P2X7 purinergic receptors (P2X7Rs). Our recent work has shown that extracellular ATP, in turn, induces clustering of Panx1 with P2X7Rs and their subsequent internalization through a non-canonical cholesterol-dependent mechanism. In other words, we have demonstrated that extracellular ATP levels can regulate the cell surface expression of Panx1. Here we discuss two situations, in which we hypothesize ATP modulation of Panx1 surface expression could be relevant for central nervous system function. The first scenario involves the development of new neurons in the ventricular zone. We propose that ATP-induced Panx1 endocytosis could play an important role in regulating the balance of cell proliferation, survival and differentiation within this neurogenic niche in the healthy brain. The second scenario relates to the spinal cord, in which we posit that an impairment of ATP-induced Panx1 endocytosis could contribute to pathological neuroplasticity. Together the discussion of these hypotheses serves to highlight important outstanding questions regarding the interplay between extracellular ATP, Panx1, and P2X7Rs in the nervous system, in health and disease.